2016
DOI: 10.3390/met6060130
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Effect on a Medium Carbon Forging Steel

Abstract: Abstract:In the present work the influence of vanadium on the hardenability and the bainitic transformation of a medium carbon steel is analyzed. While V in solid solution enhances the former, it hardly affects bainitic transformation. The results also reveal an unexpected result, an increase of the prior austenite grain size as the V content increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…For every forging, post cooling rates decide the type of matrix structure, namely, quenching, rapid cooling, and moderate cooling resulting in martensite, bainite, and ferrite-pearlite matrix structures, respectively. Microalloying of V, Ti, and/or Nb contributes to the refining of prior austenitic grain and the precipitation strengthening of the matrix structure by V,Ti,Nb(C,N)-carbonitrides [8,[38][39][40][41][42][43][44][45]. Microalloying of Cr, Mo, Ni, B, etc.…”
Section: Classification Of Hot-forging Process For Low and Medium Carmentioning
confidence: 99%
See 1 more Smart Citation
“…For every forging, post cooling rates decide the type of matrix structure, namely, quenching, rapid cooling, and moderate cooling resulting in martensite, bainite, and ferrite-pearlite matrix structures, respectively. Microalloying of V, Ti, and/or Nb contributes to the refining of prior austenitic grain and the precipitation strengthening of the matrix structure by V,Ti,Nb(C,N)-carbonitrides [8,[38][39][40][41][42][43][44][45]. Microalloying of Cr, Mo, Ni, B, etc.…”
Section: Classification Of Hot-forging Process For Low and Medium Carmentioning
confidence: 99%
“…PHFP-M steels developed as alternative materials of Q&T forging steels are characterized by low production cost due to the elimination of an additional Q&T step. The PHFP-M steels are achieved by reduction of the ferrite fraction, the decrease in the pearlite lamellae spacing, and the addition of the microalloying elements Nb and Ti, which results in additional precipitates besides the V(C,N) [3,[38][39][40]45,51,52]. However, the PHFP-M steels possess lower yield strength, lower tensile strength, and lower Charpy V-notch impact energy compared to the Q&T steels, although the yield stress and tensile strength are higher than those of the PHFP steels with 0.1 to 0.4 mass% V (Figure 3).…”
Section: Phfp-m Steelsmentioning
confidence: 99%
“…% C alloys with V additions of up to 0.4 wt. % Sourmail and co-authors [2,3] reported no significant precipitation or clustering of V and no effect on the bainite reaction for isothermal transformations in the range 375-450 • C. In fact, the dominant effect of vanadium in these alloys was a strong reduction in the critical cooling rate for pearlite formation, leading to a significant improvement in hardenability for large sections. Wang et al [4] found that the addition of 0.13 wt.…”
Section: Introductionmentioning
confidence: 97%
“…Vanadium additions are known to be beneficial for improving the strength and/or the in-use performance of several classes of advanced high strength steel (AHSS) products. These include low carbon hot rolled bainitic steels [1], medium carbon air-cooled bainitic forging steels [2][3][4], intercritically annealed low and medium carbon transformation induced plasticity (TRIP) and dual phase (DP) sheets [5], medium carbon ferritic hot strips [6,7] and high carbon austenitic twinning induced plasticity (TWIP) steels [8,9]. Classically, the vanadium strengthening effect in carbon-manganese steels is attributed to a combination of microstructure refinement and precipitation hardening [10].…”
Section: Introductionmentioning
confidence: 99%
“…The existing small carbides can coalesce and grow up under the interaction of cyclic mechanical and thermal loads during the service process [12]. Especially, the fatigue loads can accelerate the growth of M23C6 carbides [17][18][19]. In region 4, plenty of large size M23C6 carbides that are formed along the martensitic lath boundaries can decrease the impact toughness.…”
Section: Transmission Electron Microscope Analysismentioning
confidence: 99%